Low-carbon high-performance sprayed concrete and preparation method thereof

By using new mineral blends and ordinary mineral blends in spray concrete to replace some cement, the problems of mechanical properties and low carbonization of existing spray concrete are solved, and high-performance and low carbonization of spray concrete are achieved.

CN119661166APending Publication Date: 2025-03-21TONGJI UNIV

Patent Information

Application Number
CN202411589436.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

While improving the mechanical properties of existing spray concrete, it is difficult to achieve low carbonization and energy saving and emission reduction, and the high amount of mineral blends will lead to a decrease in mechanical properties.

Method used

Increase the compressive strength and early strength of sprayed concrete by replacing part of the cement with new mineral blends such as calcined clay, tailings slag or sulfaluminate cement.

Benefits of technology

The high performance and low carbonization of sprayed concrete are achieved, the compressive strength is increased by more than 25% in 8 hours, the compressive strength is greater than 15MPa in 24 hours, and the compressive strength is greater than 38MPa in 28 days, while the cement usage is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to low-carbon high-performance sprayed concrete and a preparation method thereof. The low-carbon high-performance sprayed concrete comprises the following components in parts by weight: 5-106 parts of a novel mineral admixture, 5-60 parts of a common mineral admixture, 300-500 parts of cement, 500-800 parts of sand, 600-1000 parts of stones, 0.5-4 parts of a water reducing agent, 0-5 parts of a strength accelerant, 10-50 parts of an accelerator and 100-250 parts of water. Compared with the prior art, cement is replaced by the novel mineral admixture, the potential activity of the mineral admixture is fully utilized to promote coagulation of the sprayed concrete and improve the compressive strength of the sprayed concrete, the cement replacement rate of the novel mineral admixture is 5-15%, and the cement replacement rate of the total mineral admixture is 15-30%. The early strength of the sprayed concrete doped with the mineral admixture is improved by more than 25%, and the sprayed concrete has outstanding economic, social and environment-friendly benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a low-carbon high-performance shotcrete and a preparation method thereof. Background Art

[0002] Shotcrete is often used in underground projects to stabilize tunnel walls and prevent groundwater infiltration. With the rise of railway construction and urban rail transit in my country, the demand for shotcrete has increased dramatically in recent years. During tunnel excavation, a large amount of shield clay and a large amount of tailings slag are piled up in the tailings pond. At present, the traditional method of open-air stacking or landfill is mainly used, which has the hazards of occupying land, polluting soil and groundwater, and brings great challenges to the environment. At present, reducing the amount of cement to prepare low-carbon concrete is one of the most effective methods. Mineral admixtures commonly used to replace cement include slag powder, fly ash, silica fume, etc. However, these mineral admixtures are not only difficult to obtain and expensive, but also have a negative impact on the mechanical properties of concrete, which seriously restricts the promotion and application of low-carbon concrete. Therefore, the development and promotion of high-efficiency and low-cost admixtures and the development of shotcrete with excellent performance are of great significance to improve the strength of support projects, protect the health of construction workers and reduce waste.

[0003] At present, some progress has been made in realizing the transformation of shotcrete to low carbon and high performance at home and abroad. Under the premise of meeting the "Technical Specification for the Application of Shotcrete" JGJ / T 372-2016, industrial solid waste or tailings are used to prepare new green mineral admixtures, and the cement replacement rate is 5-15%, but the cement replacement rate of the total mineral admixture is 15-30%, which is still rarely reported. This is because the excessive amount of mineral admixtures will cause its mechanical properties to drop significantly. Chinese patent CN110105012 A discloses a high-performance special admixture for shotcrete. By using a mixture of a cohesive component modified latex powder and an ultrafine mineral admixture and the synergistic effect of an early strength component, the cohesion and early strength of the shotcrete are effectively improved. However, the dosage of the special admixture in the invention is less than 10%, and the carbon reduction effect is not significant. Chinese patent CN115849764 A discloses a shotcrete admixture and its preparation method and application. The shotcrete admixture introduces a composite admixture, the composition is too complex, and the kaolin content accounts for about 50%, and the overall cost is high. Chinese patent CN117776637 A discloses an early-strength admixture for shotcrete and a method of using the same. The invention uses a special early-strength admixture, but the energy-saving and emission-reduction effect on high-performance shotcrete is not significant.

[0004] Therefore, further breakthroughs are needed in solid waste treatment and resource utilization technologies, and the use of industrial solid waste or tailings to prepare new green mineral admixtures to promote the development of shotcrete towards low carbonization and high performance. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a low-carbon high-performance shotcrete and a preparation method thereof, so as to provide an effective solution for developing high-efficiency, low-cost admixtures and developing shotcrete with excellent performance.

[0006] During the conception of the present invention: the present invention uses a new type of mineral admixture to replace cement, and fully utilizes the potential activity of the mineral admixture to promote the coagulation of the sprayed concrete and improve the compressive strength of the sprayed concrete.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] On the one hand, the present invention provides a low-carbon, high-performance shotcrete, comprising the following components in parts by weight: 5 to 106 parts of a new mineral admixture, 5 to 60 parts of a common mineral admixture, 300 to 500 parts of cement, 500 to 800 parts of sand, 600 to 1000 parts of gravel, 0.5 to 4 parts of a water reducer, 0 to 5 parts of a strength accelerator, 10 to 50 parts of an accelerator, and 100 to 250 parts of water.

[0009] Preferably, the shotcrete comprises the following components by weight: 60-75 parts of new mineral admixture, 50-60 parts of ordinary mineral admixture, 330-450 parts of cement, 700-800 parts of sand, 800-1000 parts of gravel, 3-4 parts of water reducer, 2-4 parts of strength accelerator, 15-30 parts of accelerator, and 150-200 parts of water.

[0010] Furthermore, the particle sizes of the novel mineral admixture, common mineral admixture and cement are all no greater than 75 μm.

[0011] Furthermore, the novel mineral admixture is calcined clay, tailings or sulphoaluminate cement.

[0012] Furthermore, the common mineral admixture is one or more of mineral powder, fly ash, and silica fume.

[0013] Furthermore, the sand is river sand or machine-made sand.

[0014] Furthermore, the stone is crushed stone with a gradation of 5 to 20 mm.

[0015] Preferably, the stone is crushed stone with a gradation of 5 to 10 mm.

[0016] Furthermore, the water reducer is a polycarboxylate water reducer, a naphthalene-based water reducer or a lignin sulfonate-based water reducer.

[0017] Furthermore, the strength accelerator is nano-silicon dioxide, nano-calcium carbonate or nano-CSH crystal nucleus.

[0018] Furthermore, the accelerator is an alkali-free liquid accelerator, which includes aluminum sulfate, an alcohol amine admixture and water, wherein the mass proportion of the aluminum sulfate in the alkali-free liquid accelerator is 25-55%, the mass proportion of the alcohol amine admixture in the alkali-free liquid accelerator is 5-10%, and the mass proportion of the water in the alkali-free liquid accelerator is 35-70%; the alcohol amine chemical admixture is one or more of diethanolamine, triethanolamine, and triisopropanolamine.

[0019] On the other hand, the present invention provides a method for preparing low-carbon high-performance shotcrete, comprising the following steps:

[0020] New mineral admixtures, common mineral admixtures, cement, sand, gravel, water reducer, strength accelerator and water are mixed evenly in proportion, then an accelerator is added and mixed evenly, and then the mixed slurry is poured into a mold to prepare shotcrete.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) Under the premise of meeting the "Technical Code for Application of Shotcrete" JGJ / T 372-2016, the present invention uses calcined clay, tailings or sulphoaluminate cement in the new mineral admixture for shotcrete. The new mineral admixture can partially replace cement, and its cement replacement rate is 5-15%. In the present invention, ordinary mineral admixtures are also used to partially replace cement, and the cement replacement rate of the total mineral admixture is 15-30%.

[0023] (2) The shotcrete prepared by the present invention with mineral admixtures has better mechanical properties than the shotcrete without mineral admixtures, and the 8h compressive strength is increased by more than 25%. The 8h compressive strength of C30 shotcrete is greater than 10MPa, the 24h compressive strength is greater than 15MPa, and the 28d compressive strength is greater than 38MPa.

[0024] (3) The preparation method of the shotcrete admixture provided by the present invention has the advantages of simple operation, low equipment requirements, good construction performance, green environmental protection and easy large-scale promotion and application. DETAILED DESCRIPTION

[0025] The present invention is described in detail below in conjunction with specific embodiments.It should be noted that all professional and scientific terms used in the text are identical with the meanings familiar to those skilled in the art, unless otherwise defined.In addition, the reagents or raw materials used in the present invention can be purchased through conventional channels, and if not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or according to the product specification.Features such as preparation means, materials, structures or composition ratios that are not clearly described in this technical solution are regarded as common technical features disclosed in the prior art.

[0026] The experimental raw materials used in the following examples are: cement is Conch PO42.5 ordinary Portland cement; sand is ordinary river sand with a fineness modulus of 2.6 and a particle size of less than 4.75 mm; gravel is crushed stone with a grading of 5 to 10 mm; the water reducer is a polycarboxylic acid water reducer; the accelerator is an alkali-free liquid accelerator, which is composed of 25% aluminum sulfate, 5% triethanolamine and 70% water; among them, the particle sizes of the new mineral admixtures (coal gangue powder, red mud, calcined clay, sulphoaluminate cement, tailings), ordinary mineral admixtures (silica fume, fly ash), and cement are all not higher than 75 μm.

[0027] Comparative Example 1

[0028] The tests were carried out using shotcrete without mineral admixtures.

[0029] Weigh 450 parts by weight of cement, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid quick-setting agent and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0030] Comparative Example 2

[0031] The test was conducted using shotcrete mixed with common mineral admixtures, and the cement replacement rate of the common mineral admixtures was 13.3%.

[0032] Weigh 390 parts by weight of cement, 60 parts by weight of ordinary mineral admixture, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid quick-setting agent and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0033] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0034] Comparative Example 3

[0035] The test was carried out on shotcrete mixed with new mineral admixtures and common mineral admixtures. The cement replacement rate of the common mineral admixture was 13.3%.

[0036] Weigh 330 parts by weight of cement, 60 parts by weight of coal gangue powder, 60 parts by weight of ordinary mineral admixture, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid accelerator and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0037] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0038] Comparative Example 4

[0039] The test was carried out on shotcrete mixed with new mineral admixtures and common mineral admixtures. The cement replacement rate of the common mineral admixture was 13.3%.

[0040] Weigh 330 parts by weight of cement, 60 parts by weight of red mud, 60 parts by weight of common mineral admixture, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid accelerator and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0041] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0042] Example 1

[0043] Tests were conducted on shotcrete mixed with new mineral admixtures and ordinary mineral admixtures. The cement replacement rate of the new mineral admixtures was 13.3%, the cement replacement rate of the ordinary mineral admixtures was 13.3%, and the total mineral admixture replacement rate was 26.7%.

[0044] Weigh 330 parts by weight of cement, 60 parts by weight of calcined clay, 60 parts by weight of ordinary mineral admixture, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid accelerator and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0045] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0046] Example 2

[0047] Tests were conducted on shotcrete mixed with new mineral admixtures and ordinary mineral admixtures. The cement replacement rate of the new mineral admixtures was 13.3%, the cement replacement rate of the ordinary mineral admixtures was 13.3%, and the total mineral admixture replacement rate was 26.7%.

[0048] Weigh 315 parts by weight of cement, 75 parts by weight of calcined clay, 60 parts by weight of ordinary mineral admixture, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid accelerator and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0049] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0050] Example 3

[0051] Tests were conducted on shotcrete mixed with new mineral admixtures and ordinary mineral admixtures. The cement replacement rate of the new mineral admixtures was 13.3%, the cement replacement rate of the ordinary mineral admixtures was 13.3%, and the total mineral admixture replacement rate was 26.7%. At the same time, strength promoters were added.

[0052] Weigh 330 parts by weight of cement, 60 parts by weight of calcined clay, 60 parts by weight of ordinary mineral admixture, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer, 2 parts by weight of nano-silicon dioxide and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid accelerator and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0053] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0054] Example 4

[0055] A method for preparing low-carbon high-performance concrete is the same as that of Example 3, except that the added strength accelerator is nano calcium carbonate.

[0056] Example 5

[0057] A method for preparing low-carbon high-performance concrete is the same as that of Example 3, except that the added strength accelerator is nano CSH crystal nuclei.

[0058] Example 6

[0059] Tests were conducted on shotcrete mixed with new mineral admixtures and ordinary mineral admixtures. The cement replacement rate of the new mineral admixtures was 13.3%, the cement replacement rate of the ordinary mineral admixtures was 13.3%, and the total mineral admixture replacement rate was 26.7%.

[0060] Weigh 330 parts by weight of cement, 60 parts by weight of sulphoaluminate cement, 60 parts by weight of ordinary mineral admixture, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid accelerator and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0061] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0062] Example 7

[0063] Tests were conducted on shotcrete mixed with new mineral admixtures and ordinary mineral admixtures. The cement replacement rate of the new mineral admixtures was 13.3%, the cement replacement rate of the ordinary mineral admixtures was 13.3%, and the total mineral admixture replacement rate was 26.7%.

[0064] Weigh 315 parts by weight of cement, 75 parts by weight of sulphoaluminate cement, 60 parts by weight of ordinary mineral admixture, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid accelerator and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0065] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0066] Example 8

[0067] Tests were conducted on shotcrete mixed with new mineral admixtures and ordinary mineral admixtures. The cement replacement rate of the new mineral admixtures was 13.3%, the cement replacement rate of the ordinary mineral admixtures was 13.3%, and the total mineral admixture replacement rate was 26.7%. At the same time, strength promoters were added.

[0068] Weigh 330 parts by weight of cement, 60 parts by weight of sulphoaluminate cement, 60 parts by weight of ordinary mineral admixture, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer, 2 parts by weight of nano-silicon dioxide and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid accelerator and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0069] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0070] Example 9

[0071] A method for preparing low-carbon high-performance concrete is the same as Example 8, except that the added strength accelerator is nano calcium carbonate.

[0072] Example 10

[0073] A method for preparing low-carbon high-performance concrete is the same as Example 8, except that the added strength accelerator is nano CSH crystal nuclei.

[0074] Embodiment 11

[0075] Tests were conducted on shotcrete mixed with new mineral admixtures and ordinary mineral admixtures. The cement replacement rate of the new mineral admixtures was 13.3%, the cement replacement rate of the ordinary mineral admixtures was 13.3%, and the total mineral admixture replacement rate was 26.7%.

[0076] Weigh 330 parts by weight of cement, 60 parts by weight of tailings, 60 parts by weight of ordinary mineral admixtures, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid accelerator and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0077] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0078] Example 12

[0079] Tests were conducted on shotcrete mixed with new mineral admixtures and ordinary mineral admixtures. The cement replacement rate of the new mineral admixtures was 13.3%, the cement replacement rate of the ordinary mineral admixtures was 13.3%, and the total mineral admixture replacement rate was 26.7%.

[0080] Weigh 315 parts by weight of cement, 75 parts by weight of tailings, 60 parts by weight of ordinary mineral admixture, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid accelerator and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0081] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0082] Example 13

[0083] Tests were conducted on shotcrete mixed with new mineral admixtures and ordinary mineral admixtures. The cement replacement rate of the new mineral admixtures was 13.3%, the cement replacement rate of the ordinary mineral admixtures was 13.3%, and the total mineral admixture replacement rate was 26.7%. At the same time, strength promoters were added.

[0084] Weigh 330 parts by weight of cement, 60 parts by weight of tailings, 60 parts by weight of ordinary mineral admixture, 754 parts by weight of river sand, 896 parts by weight of gravel, 4 parts by weight of water reducer, 2 parts by weight of nano-silicon dioxide and 180 parts by weight of water, mix them evenly, then add 25 parts by weight of alkali-free liquid accelerator and mix them evenly, then pour the above mixed slurry into a mold to prepare a shotcrete test block.

[0085] Among them, the common mineral admixtures include silica fume and fly ash, with the silica fume accounting for 10 parts by weight and the fly ash accounting for 50 parts by weight.

[0086] Embodiment 14

[0087] A method for preparing low-carbon high-performance concrete is the same as Example 13, except that the added strength accelerator is nano calcium carbonate.

[0088] Embodiment 15

[0089] A method for preparing low-carbon high-performance concrete is the same as Example 15, except that the added strength promoter is nano CSH crystal nuclei.

[0090] The sprayed concrete test blocks prepared in Comparative Examples 1-4 and Examples 1-15 were subjected to performance tests. First, the setting time of the sprayed concrete test blocks was tested. Then, the test blocks were cured in a standard curing room (20±3°C, humidity>95%) for 8h, 1 day, 3 days and 28 days, and the strength of the test blocks at different ages was tested using a press. The results are shown in Tables 1-4.

[0091] Table 1 Shotcrete performance of comparative examples 1-4

[0092] Serial number Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Final setting time 7min20s 6min50s 7min10s 6min30s 8h compressive strength / MPa 8.5 6.7 5.5 3.2 1d compressive strength / MPa 18.1 16.5 13.3 9.8 3d compressive strength / MPa 29.8 27.6 22.5 18.9 28d compressive strength / MPa 43.1 41.5 40.8 36.7

[0093] Table 2 Performance of shotcrete with calcined clay as the new mineral admixture in Examples 1-5

[0094] Serial number Example 1 Example 2 Example 3 Example 4 Example 5 Final setting time 5min30s 4min55s 5min20s 4min50s 4min40s 8h compressive strength / MPa 12.6 11.2 12.8 13.1 15.8 1d compressive strength / MPa 20.5 18.7 21.1 22.6 24.9 3d compressive strength / MPa 31.7 29.9 31.9 33.4 36.5 28d compressive strength / MPa 45.3 43.2 45.5 46.7 48.6

[0095] Table 3 Performance of shotcrete with new mineral admixture of sulphoaluminate cement in Examples 6-10

[0096] Serial number Example 6 Example 7 Example 8 Example 9 Example 10 Final setting time 5min40s 4min 45s 5min30s 4min50s 3min25s 8h compressive strength / MPa 11.5 10.8 11.7 12.5 13.6 1d compressive strength / MPa 21.3 18.3 21.8 21.5 21.6 3d compressive strength / MPa 34.7 29.6 35.1 35.7 35.8 28d compressive strength / MPa 46.9 38.9 46.8 47.2 47.7

[0097] Table 4 Performance of shotcrete with tailings as new mineral admixture in Examples 11-15

[0098] Serial number Embodiment 11 Example 12 Example 13 Embodiment 14 Embodiment 15 Final setting time 6min10s 5min45s 5min50s 5min20s 4min55s 8h compressive strength / MPa 11.1 10.7 11.6 11.9 12.6 1d compressive strength / MPa 19.6 18.3 20.4 20.5 21.3 3d compressive strength / MPa 30.8 28.6 31.1 31.2 32.4 28d compressive strength / MPa 43.9 39.7 44.2 44.3 44.5

[0099] As can be seen from Tables 1-4, compared with Comparative Examples 1 and 2, the mechanical properties of the shotcrete prepared by adding the new mineral admixture in Examples 1, 6, and 11 are significantly better, and the setting time is also significantly shortened. This is mainly because calcined clay has better volcanic ash activity, sulphoaluminate cement can promote early cement hydration, and tailings have a good filling effect, which enables the concrete to set quickly, increases the content of hydration products, and makes the microstructure of the concrete more compact, thereby increasing the mechanical properties of the shotcrete prepared in Examples 1, 6, and 11. At the same time, compared with the new mineral admixtures such as coal gangue powder and red mud in Comparative Examples 3 and 4, the addition of calcined clay, sulphoaluminate cement and tailings significantly improves the performance of shotcrete, which is mainly because the new mineral admixture proposed by the present invention has a higher activity.

[0100] As can be seen from Tables 2-4, by comparing Examples 1 and 2, Examples 6 and 7, and Examples 11 and 12, it is found that the optimal dosage of the new mineral admixture is 60 parts by weight. When the cement replacement rate of the new mineral admixture is 13.3%, the compressive strength of the shotcrete is higher. This may be due to the further increase of the new mineral admixture to 16.7%. Its activity is lower than that of cement, which reduces the compressive strength. However, when the cement replacement rate of the total mineral admixture is 30%, the compressive strength is still higher than that of Comparative Examples 1-4, and the energy-saving and emission-reduction effects are also better than those of Comparative Examples 1-4.

[0101] By comparing Examples 1 and 3-4, Examples 6 and 8-10, and Examples 11 and 13-15, it is found that after adding strength accelerators to Examples 3-4, Examples 8-10, and Examples 13-15, the setting time of the prepared shotcrete is shortened and the compressive strength is increased. This is mainly because the nanoparticles can provide nucleation sites, further accelerate cement hydration, make the concrete microstructure more compact, and ultimately effectively improve the compressive strength of the concrete.

[0102] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A low-carbon high-performance shotcrete, characterized in that: The invention comprises the following components in parts by weight: 5-106 parts of new mineral admixture, 5-60 parts of common mineral admixture, 300-500 parts of cement, 500-800 parts of sand, 600-1000 parts of gravel, 0.5-4 parts of water reducing agent, 0-5 parts of strength accelerator, 10-50 parts of quick-setting agent and 100-250 parts of water.

2. A low-carbon high-performance shotcrete according to claim 1, characterized in that: The particle sizes of the novel mineral admixture, common mineral admixture and cement are all no greater than 75 μm.

3. The low-carbon high-performance shotcrete according to claim 1, characterized in that: The novel mineral admixture is calcined clay, tailings or sulphoaluminate cement.

4. The low-carbon high-performance shotcrete according to claim 1, characterized in that: The common mineral admixture is one or more of mineral powder, fly ash and silica ash.

5. The low-carbon high-performance shotcrete according to claim 1, characterized in that: The sand is river sand or machine-made sand.

6. The low-carbon high-performance shotcrete according to claim 1, characterized in that: The stone is crushed stone with a gradation of 5 to 20 mm.

7. The low-carbon high-performance shotcrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer, a naphthalene water reducer or a lignin sulfonate water reducer.

8. The low-carbon high-performance shotcrete according to claim 1, characterized in that: The strength accelerator is nano silicon dioxide, nano calcium carbonate or nano CSH crystal nucleus.

9. The low-carbon high-performance shotcrete according to claim 1, characterized in that: The accelerator is an alkali-free liquid accelerator, which includes aluminum sulfate, an alcohol amine admixture and water, wherein the weight proportion of the aluminum sulfate in the alkali-free liquid accelerator is 25-55%, the weight proportion of the alcohol amine admixture in the alkali-free liquid accelerator is 5-10%, and the weight proportion of the water in the alkali-free liquid accelerator is 35-70%; The alcoholamine chemical additive is diethanolamine, triethanolamine or triisopropanolamine.

10. A method for preparing low-carbon high-performance shotcrete as claimed in claims 1 to 9, characterized in that: The following steps are involved: New mineral admixtures, common mineral admixtures, cement, sand, gravel, water reducer, strength accelerator and water are mixed evenly in proportion, then an accelerator is added and mixed evenly, and then the mixed slurry is poured into a mold to prepare shotcrete.

Citation Information

Patent Citations

  • Admixture special for high performance shotcrete

    CN110105012A

  • Sprayed concrete admixture as well as preparation method and application thereof

    CN115849764A

  • Early-strength admixture for sprayed concrete and use method of early-strength admixture

    CN117776637A

Cited By

  • High-performance shotcrete for tunnel with water-rich surrounding rock and preparation method thereof

    CN122831623A